The research on educational environment of institution of higher education involving experts: results and analysis - Bratko Mariia; Khoruzha Liudmyla (SHS Web of Conferences, 2020)
Based on the analysis of scientific resources, the role of educational environment in personal building, development and education is actualized. It is stated that educational environment is one of the most essential factors of those processes. The author’s definitions of notions “educational environment”, “educational environment of institution of higher education” are given. The authors advocate the point that educational environment is a system of facilities for personal education. It is emphasized that the environmental approach in education is changing accents in teaching which is aimed at creating and developing educational environment, which has to meet educational needs of a student. The author’s technique of evaluating the state of educational environment of institution of higher education is grounded and approved, the rating scale of this technique is introduced. The technique suggests making expert evaluation of educational environment of institution of higher education according to qualitative (modality) and quantitative (professional breadth, professional saturation, sociocultural intensity, congruence, openness, mobility, informativeness) parameters. The typology of educational environment of institution of higher education is presented (innovative-professional, formal-professional, pragmatically-oriented, formal general cultural educational environment). The analysis and interpretation of the results obtained from the experiment at University College of Borys Grinchenko Kyiv University are given. The evaluation of educational environment of the college has been made by three groups of experts, which have included students, teachers and parents. Despite the fact that evaluation by different groups of experts are similar, it is revealed that it has essential differences, which has been proved with appropriate statistical methods. It is determined that the substantiation of the whole monitoring system of educational environment of institution of higher education and corresponding diagnostic tools has great potential.